2021
DOI: 10.1021/acsami.1c03696
|View full text |Cite
|
Sign up to set email alerts
|

Self-Templated Formation of Fluffy Graphene-Wrapped Ni5P4 Hollow Spheres for Li-Ion Battery Anodes with High Cycling Stability

Abstract: Transition-metal phosphides have gained great importance in the field of energy conversion and storage such as electrochemical water splitting, fuel cells, and Li-ion batteries. In this study, a rationally designed novel fluffy graphene (FG)wrapped monophasic Ni 5 P 4 (Ni 5 P 4 @FG) is in-situ-synthesized using a chemical vapor deposition method as a Li-ion battery anode material. The porous and hollow structure of Ni 5 P 4 core is greatly helpful for lithium-ion diffusion, and at the same time, the cilia-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Impressively, the serious volume changes would induce the continuous generation and broken of solid electrolyte interface (SEI) layers, [ 39 , 40 ] thus consuming the electrolyte and degrading the cyclic stability and Coulumbic efficiency (CE). [ 41 , 46 ] To resolve these pressing issues, the promising strategies included the hybridization of phosphorus‐ and phosphide‐based materials with conductive materials (e.g., carbonaceous materials and conductive polymers) and constructing unique micro‐ and nanostructures, [ 42 , 49 ] which can boost the electron transfer, provide enough space for volume changes and enhance the entire structural integrity of electrode.…”
Section: Working Principles and Challenges Of Phosphorus‐ And Phosphi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Impressively, the serious volume changes would induce the continuous generation and broken of solid electrolyte interface (SEI) layers, [ 39 , 40 ] thus consuming the electrolyte and degrading the cyclic stability and Coulumbic efficiency (CE). [ 41 , 46 ] To resolve these pressing issues, the promising strategies included the hybridization of phosphorus‐ and phosphide‐based materials with conductive materials (e.g., carbonaceous materials and conductive polymers) and constructing unique micro‐ and nanostructures, [ 42 , 49 ] which can boost the electron transfer, provide enough space for volume changes and enhance the entire structural integrity of electrode.…”
Section: Working Principles and Challenges Of Phosphorus‐ And Phosphi...mentioning
confidence: 99%
“…However, similar to pure phosphorus, phosphides suffered from low electrical conductivity and significant volume expansion. Hybridizing phosphides with carbonaceous materials can solve the above issues, and the adopted carbonaceous materials include graphene, [ 49 ] carbon nanotubes (CNTs), [ 50 ] and porous carbon matrices. [ 51 ] For instance, Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the conversion reaction process can be expressed as follows: MP + xLi + + e ─ → Li 3 P + M (where M represents transition metals). [25][26][27] However, the in-depth mechanistic contribution of the CFC was not emphasized. 17,28 Compared to CoP, nickel phosphides have also been utilized as electrode materials for energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 BTMPs have the advantages of high conductivity, earth-abundant reserves, and good physicochemical properties. 4,5 However, the lack of high activity and unstable structure of BTMPs are the main obstacles to their practical applications in energy storage fields. Many efforts have been devoted to improving their activity and stability, including (1) modulation of active sites through heteroatom doping and vacancy engineering 6−8 and (2) multicomponent and multidimensional structure design of nanocomposites and morphology.…”
mentioning
confidence: 99%
“…Binary transition metal phosphides (BTMPs) consisting of phosphorus with d and f metals are widely used in electrocatalysis, photocatalysis, and electrochemistry. , BTMPs have the advantages of high conductivity, earth-abundant reserves, and good physicochemical properties. , However, the lack of high activity and unstable structure of BTMPs are the main obstacles to their practical applications in energy storage fields. Many efforts have been devoted to improving their activity and stability, including (1) modulation of active sites through heteroatom doping and vacancy engineering and (2) multicomponent and multidimensional structure design of nanocomposites and morphology. These conventional methods are usually cumbersome and do not have significant effects.…”
mentioning
confidence: 99%